Basketball GOATs : the greatest athletes of all time - Berglund, Bruce R. (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2022)
How do you pick basketball's GOATs? Michael Jordan and LeBron James get a lot of GOAT nods. But is Steph Curry the greatest shooter? And what about all-time WNBA points leader Diana Taurasi? It comes down to stats, history, and hunches. Read more about some of the legends of basketball and see if you agree that they're the greatest of all time.
Basketball--a sport of stars -- Basketball's biggest stars -- Greatest shooters -- Greatest champions -- Greatest all-around players.
Includes bibliographical references (page 31) and index.
4.1
3-6
810L
Keywords: Basketball players -- United States -- Juvenile literature; National Basketball Association -- Juvenile literature; Women's National Basketball Association -- Juvenile literature; Basketball players; National Basketball Association; Women's National Basketball Association; Women basketball players -- Juvenile literature